Corrigendum. (March 2017) - Unknown
Zarrin M and Azadeh A. Simulation optimization of lean production strategy by considering resilience engineering in a production system with maintenance policies. Simulation . Epub ahead of print 8 September 2016. DOI:10.1177/0037549716666682 In this article, the second author was left off in error in the original OnlineFirst version. The latest online version has been corrected to reflect this. The corresponding author in the original OnlineFirst version was also incorrect. The latest online version has been corrected to display Professor Ali Azadeh as the corresponding author.